Proposed new interior design of green building index office and centre for Green Building Index Sdn. Bhd. (GSB) at 25 Jalan Sultan Ismail, 50250 Kuala Lumpur / Muhammad Syahmie Mustapha - Mustapha, Muhammad Syahmie (Faculty of Architecture, Planning and Surveying, 2011)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for my final project is Proposed New Interior Design of Green Building Index Office and Centre for Green Building Index Sdn, Bhd. at 25 Jalan Sultan Ismail, 50250 Kuala Lumpur. This proposed office and centre is moving the current GBI office to a new place since the current office is situated at PAM office. The centre will be used to promote and provide information to architect, builder and student about green building. The proposed centre is to promote to the community about green technology and building since Malaysia is still new with green technology. There are only several buildings that have been certified as green building from GBI in Malaysia. The GBI centre also use as a benchmark or example for green building.